Spectrophotometric and Conductometric Analysis of Cerium-Ofloxacin Complex - Mishra, Shobha; Yadav, Manjiri (Asian Journal of Chemistry, 2016)
A simple spectrophotometric method for the estimation of ofloxacin through the formation of complex with cerium has been developed. The yellow coloured complex has a λmax at 243 nm and obeys Beer's law in the concentration range 0 to 22 mg/mL. The stoichiometry of the complex has been determined by spectrophotometric and conductometric methods. The formation of the complex is not affected by change in pH. Being a simple, rapid and economical method it can be used in routine laboratory work.